2021
DOI: 10.3389/fmicb.2021.759432
|View full text |Cite
|
Sign up to set email alerts
|

Apart From the Diet, the Ruminal Microbiota of Lambs Is Modified in Relation to Their Genetic Potential for Feed Efficiency or Feeding Behavior

Abstract: Using two successive types of diets (100% concentrate and 67% forage), this study explores the relationship between the ruminal microbiota of 78 Romane lambs and their feed efficiency (residual feed intake trait) or feeding behavior (feeding rate trait). Analysis was carried out phenotypically by correlating feed efficiency or feeding behavior traits with the relative abundance of bacteria at the phylum, family, and genus levels, and then genetically by comparing the microbiota of lambs selected for extreme br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Similarly, the component and abundance of intestinal microbiota confer the constituents and contents of metabolites in the gut content. 33 The predicted differential metabolic pathways by comparing differentiated metabolites in the KEGG database primarily referred to the vitamin and amino acid metabolism (vitamin B 6 , tryptophan, nicotinate, and nicotinamide metabolism and lysine degradation) and bile acid biosynthesis in the LJPS group compared to those in the con group. Of these, vitamin B 6 , tryptophan, nicotinate, and nicotinamide metabolism and lysine degradation were upregulated, whereas bile acid biosynthesis was downregulated in the LJPS group compared to those in the con group.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the component and abundance of intestinal microbiota confer the constituents and contents of metabolites in the gut content. 33 The predicted differential metabolic pathways by comparing differentiated metabolites in the KEGG database primarily referred to the vitamin and amino acid metabolism (vitamin B 6 , tryptophan, nicotinate, and nicotinamide metabolism and lysine degradation) and bile acid biosynthesis in the LJPS group compared to those in the con group. Of these, vitamin B 6 , tryptophan, nicotinate, and nicotinamide metabolism and lysine degradation were upregulated, whereas bile acid biosynthesis was downregulated in the LJPS group compared to those in the con group.…”
Section: ■ Resultsmentioning
confidence: 99%
“…This certified that the increased abundance of the microbes in the LJPS-fed group enhanced the level of pyridoxal, nicotinate ribonucleoside, nicotinamide, pyridoxamine, 2-isobutyl-3-methoxypyrazine, and 2-(formylamino)­benzoic acid in intestine content, which further improved the productivities, feed efficiency, and health parameters of the ducks. Similarly, the component and abundance of intestinal microbiota confer the constituents and contents of metabolites in the gut content . The predicted differential metabolic pathways by comparing differentiated metabolites in the KEGG database primarily referred to the vitamin and amino acid metabolism (vitamin B 6 , tryptophan, nicotinate, and nicotinamide metabolism and lysine degradation) and bile acid biosynthesis in the LJPS group compared to those in the con group.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that increased microbes in the PTMR group affected the enhanced content of tyrosine, methionine, cysteine, histidine, and indole in the rumen of lambs, which further facilitated the improved performance and G/F of lambs. Similarly, it has been documented that the composition and structure of ruminal microbiota defined the constituents and contents of small molecular metabolites of rumen content ( Morgavi et al, 2015 ; Marie-Etancelin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Feed efficiency is a crucial economic indicator in pig production, especially for growing pigs. Generally, the assessment of the factors affecting feed efficiency mainly focuses on the microbiome, genetic selection, and diets [ 19 , 20 ]. However, the digestive ability of animals might be highly correlated to the feed efficiency of farm animals.…”
Section: Discussionmentioning
confidence: 99%